Impacto del Producto Interno Bruto sobre la migración en el Ecuador, periodo 1990 – 2020 - Ortega Saraguro, Josselyn Andreina (2023)
In the world, according to an estimate made in 2020, approximately 3.6% of the world's population will have migrated to a country other than their native country, that is, 281 million international migrants. Therefore, the present research aims to analyze the impact of the Gross Domestic Product and the effect on migration in Ecuador, period 1990 -2020. For this, porpuse, data from the National Institute of Statistics and Censuses [INEC] (2021) and the World Bank [WB] (2021) were used. In the methodoly, an Ordinary Least Squares (OLS) model was applied to determine the impact of GDP on migration in Ecuador, and a Granger test was developed to establish the causal relationship between the variables studied. With this, it was found that the GDP has a positive and statistically significant impact on migration, and it was also verified that the GDP causes migration in a unidirectional manner. Finally, it is recommended that the government, and private companies, and companies attracted by foreign direct investment promote the formation of human capital through training to help them improve their knowledge, so that they remain in Ecuador, thus promoting economic growth.